Art therapy with physical conditions - Liebmann, Marian, 1942-; Weston, Sally (Online access with DDA: Askews (Medicine), 2015)
As the emotional components of physical illnesses become more recognised, there is a renewed interest in the potential of art therapy to help patients come to terms with injury, pain and terminal and life-long conditions. A wide range of experienced art therapists describe their work and its benefits to a variety of groups including those with cancer, debilitating conditions such as myalgic encephalopathy (M.E.) and ulcerative colitis. Physical conditions in combination with other factors such as homelessness or learning disabilities, and children with life-long and chronic conditions are also covered. The book includes discussion of spiritual and philosophical issues when mortality is faced, life change and adjustment issues, practical considerations and which models of practice art therapists find most helpful with various groups. This will be essential reading for arts therapists and students, as well as for professionals with an interest in psychological issues and wellbeing for patients with physical illness or long term conditions, such as psychotherapists and counsellors, complementary therapists, doctors, nurses and other healthcare professionals.